Heavy Metals Contamination Through Industrial Effluent to Irrigation Water in Gadoon Amazai (Swabi) and Hayatabad (Peshawar) Pakistan - Amin, N.; Ayaz, M.; Alam, S.; Gul, S. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Industrial effluents mixed water used for irrigation in vegetable growing area was tested for its heavy metal contents using Atomic Absorption Spectrophotometry. Sixteen water samples from different industrial outlets were collected and analyzed for different physical and chemical parameters such as temperature, electrical conductivity, pH, total dissolved solids and heavy metals, in the year 2011. The results showed Cu to be in the range of 0.102-0.260, Co 0.021-0.195, Fe 0.191-0.330, Pb 0.117-0.330, Cr 0.024-0.121, Mn 0.053-0.234, Zn 0.090-0.165 and Ni as 0.019-0.074 ppm. The overall metal concentration in the studied samples was in the order of Fe>Pb>Cu>Mn>Co>Zn>Cr>Ni (p < 0.05). pH was in the range of 3.1-8.7 and electrical conductivity was 325 to 1515 ms/cm. As all values were found to be increasing towards pollution limits, industrial effluents need a continuous monitoring and proper management before their discharge in order to reduce the future hazards in reference to aquatic and human life. Keywords: Industrial effluents; Irrigation water; Heavy metals; Pollution. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.16336 J. Sci. Res. 6 (1), 111-124 (2014) <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->